Revised potential field model of the Gilmore Fault Zone - Venkataramani, D.; Musgrave, R.; Boutelier, D.; Hack, A.; Collins, Bill (CSIRO Publishing, 2017)
The Gilmore Fault Zone (GFZ) marks a distinct geophysical contrast between metasediments of the Wagga Metamorphic Belt (high gravity and low magnetic intensity) and the Macquarie Arc and Silurian rift basins (low gravity and high magnetic intensity) in the Eastern Lachlan Orogen, Australia. This study uses a geologically constrained inversion of magnetic and gravity data to provide a revised model of the GFZ. This model results in a significant improvement in fit to all previous models of the same profiles and involves repeated two-way exchange between geologists and geophysicists. Two profiles corresponding to the seismic reflection lines 99AGSL1-L2 and 99AGSL3, and extending for more than 80 km, were simultaneously inverted by forward modelling of total magnetic intensity and gravity data. This was done through iterative modification of body geometry correlating to mapped geology. Profiles were further constrained by reflection seismics and physical property contrasts. This model is used to clearly define the dip direction of the GFZ (west-dipping) and suggests a separate classification of the Barmedman Fault (east-dipping). The Barmedman Fault is a shallow fault flake, previously considered part of the GFZ, which has contributed to the confusion around the regional extent of the GFZ. This new work also has the potential to inform future tectonic interpretations of this area.